Low‐grade inflammation is associated with lower haemoglobin levels in healthy individuals: results from the Danish blood donor study. Issue 2 (7th March 2016) - Kotzé, S. R.; Pedersen, O. B.; Petersen, M. S.; Sørensen, E.; Thørner, L. W.; Sørensen, C. J.; Rigas, A. S.; Hjalgrim, H.; Rostgaard, K.; Ullum, H.; Erikstrup, C.
Abstract : Background and Objectives: Chronic inflammation can lead to anaemia of chronic disease due to the sequestration of iron caused by inflammatory cytokines and the protein hepcidin. However, the effect of low‐grade inflammation (LGI) on haemoglobin among healthy individuals is not known. This study examines the effect of LGI on haemoglobin among Danish blood donors. Materials and Methods: We performed multivariable linear regression to assess the effect of LGI (i.e. high‐sensitivity C‐reactive protein above 3 mg/l but below 10 mg/l) on haemoglobin in 17 322 Danish blood donors. We also performed multivariable logistic regression to evaluate the effect of LGI on the risk of having low haemoglobin (below the 10th percentile among men and women, respectively). We adjusted for donation activity, age, sex, low ferritin, oral contraceptives and menopause. All analyses were stratified by current smoking status. Results: LGI was associated with lower haemoglobin (0·08 mm lower [0·12 g/dl], 95% confidence interval (CI): −0·11–0·05) and increased risk of low haemoglobin (OR = 1·22, 95% CI: 1·05–1·43) in non‐smokers. Conversely, LGI was associated with higher haemoglobin in smokers (0·12 mm [0·19 g/dl], 95% CI: 0·06–0·18). Conclusion: In this first study of LGI and haemoglobin in healthy individuals, there was a negative association between LGI and haemoglobin in non‐smokers. The association was positive in smokers, probably because smoking leads to both increased inflammation and increased haemoglobin through CO exposure.